Casas para os que morrem: a história do desenvolvimento dos hospices modernos Homes for the dying: the history of the development of modern hospices - Ciro Augusto Floriani; Fermin Roland Schramm (História, Ciências, Saúde: Manguinhos)
Retrata os primeiros hospices modernos, no Reino Unido vitoriano tardio, descrevendo a filosofia reinante e as dificuldades dessas instituições. Aborda, também, a fundação do St. Christopher's Hospice, considerado o marco do nascimento do moderno movimento hospice, bem como o desenvolvimento desse movimento até os dias atuais. Seu surgimento ocorre em cenário de crescente valorização tecnológica e à margem das prioridades do sistema de saúde britânico, em período de intensas transformações nas sociedades ocidentais. No Brasil, descreve como surgiu o primeiro hospice, na cidade do Rio de Janeiro, em 1944. Finaliza com um panorama atual do moderno movimento hospice no Brasil, além de considerações acerca das dificuldades para sua inserção no sistema de saúde. This portrayal of the first modern hospices, established in late Victorian Great Britain, describes the philosophy of that day and the problems faced by these institutions. It looks both at the founding of St. Christopher's Hospice, landmark of the birth of the modern hospice movement, and at the continued development of this movement down through today. The movement emerged at a time of growing appreciation for technology, outside the priorities of the British healthcare system, and during a period of major changes in Western societies. The article also describes how Brazil's first hospice came into being in Rio de Janeiro in 1944. It concludes with a current overview of the modern hospice movement in Brazil, along with thoughts on the challenges of how hospices fit within the healthcare system.